Perbandingan Tingkat Kesehatan Bank Pemerintah, Bank Swasta Nasional, dan Bank Swasta Asing Periode 2007-2011 - , Deby Devita Debora Saragih, Dra. Sri Handaru Yuliati, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An effort to improve the performance of the banking becomes very important and vital for national development, because the banks have been recognized that they have an important role in developing the national economy. Bank Indonesia set of banking performance assessment carried out by measuring the level of bank health. Bank Rating conducted by Risk approach - Based Bank Rating, with a range of assessment including the risk profile (risk profile), Corcopate Good Governance (GCG), Profitability (earnings), and Capital (capital). Different ownership from each bank determines the policy and the way of managing (management) for each banks itself, and could give different impact to the result in their health for each bank. This study aims to compare the health of banks, private banks and foreign banks, with the sample for each - each group of banks amounted to 4 (four) banks. Analysis technique used is One Way Anova. The results of this study indicate, foreign banks have high levels of credit risk, market risk and liquidity risk is higher than the state banks and foreign banks. But foreign banks also generate the highest return on assets than the other three banks, although the acquisition of its NIM smallest. This is indicative of the efficiency occurs at a foreign bank, where foreign banks can reduce the cost of issuance. From the results of statistical tests obtained significant differences in the Non - performing loans, exposure to market risk and liquidity risk exposure between the government banks, private banks and foreign banks. While on the Return On Assets (ROA), Net Interest Margin (NIM), and CAR / CAR, no significant differences between groups of banks, private banks and foreign banks.